2020
DOI: 10.1002/suco.202000194
|View full text |Cite
|
Sign up to set email alerts
|

Research on uniaxial compressive behavior of high‐strength spiral stirrups confined circular ultra‐high performance concrete columns

Abstract: To study the uniaxial compressive behavior and constitutive relationship of high‐strength spiral stirrups confined circular ultra‐high performance concrete (UHPC) columns, an experimental investigation was presented. In this research, 14 confined UHPC columns and seven unconfined UHPC columns were tested to investigate the effects of the stirrup spacing, stirrup yield strength, and steel fibers volume content on the compressive behavior of the UHPC columns. The test results indicated that transverse reinforcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, many experimental and numerical studies have been devoted to high‐performance materials, such as UHPC, ECC, and other high‐strength steel materials. Li et al 11 studied the uniaxial compressive behavior and constitutive relationship of high‐strength spiral stirrups confined in circular ultra‐high‐performance concrete (UHPC) columns. The test results indicated that transverse reinforcement can effectively improve the deformation capacity of the UHPC columns, and all confined UHPC columns showed ductile failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many experimental and numerical studies have been devoted to high‐performance materials, such as UHPC, ECC, and other high‐strength steel materials. Li et al 11 studied the uniaxial compressive behavior and constitutive relationship of high‐strength spiral stirrups confined in circular ultra‐high‐performance concrete (UHPC) columns. The test results indicated that transverse reinforcement can effectively improve the deformation capacity of the UHPC columns, and all confined UHPC columns showed ductile failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using confined concrete constitutive models have focused more on ultra-high performance concrete (UHPC) cases (Chang et al, 2020;Li et al, 2020). By contrast, stress-strain curves for lightweight concrete using recycled plastic aggregate have been studied only on a limited scale in the laboratory.…”
Section: Introductionmentioning
confidence: 99%